2016
DOI: 10.1111/jocd.12292
|View full text |Cite
|
Sign up to set email alerts
|

An efficacy and safety of nanofractional radiofrequency for the treatment of striae alba

Abstract: Nanofractional RF is highly effective with a good safety profile for the treatment of striae alba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
1
13
0
3
Order By: Relevance
“…A significant improvement in all histopathological aspects (increased epidermal thickness, dermal collagen content, and elastin content) was noticed on both sides of the abdomen after our treatment. These histopathological findings are similar to those observed in previous studies utilizing bipolar RF alone 23,24 or intradermal injection of PRP alone 25 or FMR in combination with CO 2 laser 10 in the treatment of SD. Consistent with these data, high expression levels of TGF-b1 in the epidermis and dermis were observed in the treated sites.…”
Section: Discussionsupporting
confidence: 89%
“…A significant improvement in all histopathological aspects (increased epidermal thickness, dermal collagen content, and elastin content) was noticed on both sides of the abdomen after our treatment. These histopathological findings are similar to those observed in previous studies utilizing bipolar RF alone 23,24 or intradermal injection of PRP alone 25 or FMR in combination with CO 2 laser 10 in the treatment of SD. Consistent with these data, high expression levels of TGF-b1 in the epidermis and dermis were observed in the treated sites.…”
Section: Discussionsupporting
confidence: 89%
“…Deficiency of fibrillin was reported to have a crucial role in SD histogenesis 11 . Many types of minimally invasive procedures are at hand for management of SD including; skin needling, microdermabrasion, chemical peels, mesotherapy, platelet‐rich plasma, stem cell therapy, soft tissue fillers, nonablative light‐based rejuvenation, fractional photo‐thermolysis, radiofrequency, and carboxytherapy 12‐17 …”
Section: Introductionmentioning
confidence: 99%
“…11 Many types of minimally invasive procedures are at hand for management of SD including; skin needling, microdermabrasion, chemical peels, mesotherapy, platelet-rich plasma, stem cell therapy, soft tissue fillers, nonablative light-based rejuvenation, fractional photo-thermolysis, radiofrequency, and carboxytherapy. [12][13][14][15][16][17] Carbon dioxide therapy (CDT) or carboxytherapy refers to subcutaneous or transcutaneous administration of CO 2 to produce therapeutic actions, which enhance microcirculation and tissue oxygenation. 18,19 CO 2 is an odorless, colorless gas that if injected intradermally or subcutaneously, diffuses at the skin microcirculatory level.…”
mentioning
confidence: 99%
“…Pongsrihadulchai et al have found statistically significant reduction in dimensions and total surface area of SD with nano-fractional RF. [66] These changes were reflected histopathologically by increase in average mean number of collagen and elastin bundles. A fractional ablative micro-plasma RF roller device (by Alma lasers, Israel) for SD was used by Mishra et al in five patients; the study concluded that there was improvement in the appearance of abdomen striae with this newer device.…”
Section: Copper-bromide Lasermentioning
confidence: 99%